Evaluation of Drug Management of Pharmacy Installation at Universitas Sumatera Utara Hospital - Sari, Syilvi Rinda; Khairunnisa; Aminah Dalimunthe (Talenta Publisher, 2020)
Evaluation of Drug Management of Pharmacy Installation at Universitas Sumatera Utara Hospital